In vitro evaluation of veneering composites and fibers on the color of fiber-reinforced composite restorations. - Masoomeh Hasani Tabatabaei; Zahra Hasani; Elham Ahmadi (Tehran University of Medical Sciences, 2014)
Color match between fiber-reinforced composite (FRC) restorations and teeth is an imperative factor in esthetic dentistry. The purpose of this study is to evaluate the influence of veneering composites and fibers on the color change of FRC restorations.Glass and polyethylene fibers were used to reinforce a direct microhybrid composite (Z250, 3M ESPE) and a microfilled composite (Gradia Indirect, GC). There were eight experimental groups (n=5 disks per group). Four groups were used as the controls (non-FRC control) and the others were used as experimental groups. CIELAB parameters (L*, a* and b*) of specimens were evaluated against a white background using a spectrophotometer to assess the color change. The color difference (ΔE*) and color coordinates were (L*, a* and b*) analyzed by two-way ANOVA and Tukey's test.Both types of composite and fiber influenced the color parameters (ΔL*, Δa*). The incorporation of fibers into the composite in the experimental groups made them darker than the control groups, except in the Gradia Indirect+ glass fibers group. Δb* is affected by types of fibers only in direct fiber reinforced composite. No statistically significant differences were recognized in ΔE* among the groups (p>0.05).The findings of the present study suggest that the tested FRC restorations exhibited no difference in color in comparison with non-FRC restoration. Hence, the types of veneering composites and fibers did not influence the color change (ΔE*) of FRC restorations.